Beluga whales (Delphinapterus leucas), environmental change and marine protected areas in the Western Canadian Arctic. (15th November 2018) - Loseto, L.L.; Hoover, C.; Ostertag, S.; Whalen, D.; Pearce, T.; Paulic, J.; Iacozza, J.; MacPhee, S.
Abstract: Two Arctic Marine Protected Areas (MPAs) (Tarium Niryutait and Anguniaqvia niqiqyuam) have been established in the Western Canadian Arctic, including the first in the Arctic, with conservation objectives directed to protect and maintain healthy beluga ( Delphinapterus leucas ) populations. The MPAs support the continued access of Inuvialuit (Western Arctic Inuit) to harvest beluga whales for food security and cultural purposes. The land claim and co-management framework for the Inuvialuit Settlement Region support the long term monitoring and management plans for this beluga population. We draw upon over 40 years of monitoring of the Eastern Beaufort Sea (EBS) beluga whale population and consider the utility of biological indicators for MPA management. In particular we focus on the conservation of a beluga population whose home range extends far beyond MPA boundaries (transboundary population with summer core area in excess of 36, 000 Km 2 ). We conclude that the EBS beluga whales are effective indicators of environmental change, but that we have limited understanding of the temporal and spatial relationships between beluga responses to processes that drive environmental change. Management bodies are challenged with implementing indicators that measure the impacts of 'non-manageable' stressors such as climate change, and by uncertainty in the mechanistic relationships that drive biological indicators. Given that Inuvialuit continue to be astute observers of the environment and changing conditions, our assessment suggests that Indigenous knowledge will continue to enhance the development and interpretation of beluga whale indicators for use in MPA monitoring and management.